Neuropsychological predictors of the outcome in non-demented subjects with cognitive complaints - Silva, Dina Lúcia Gomes da, 1981- (2013)
Tese de doutoramento, Ciências Biomédicas (Neurociências), Universidade de Lisboa, Faculdade de Medicina, 2012